For questions 1 through 3, you must plug-in the number for the variable into the equation. The variable is the letter that stands for an unknown value, in the case of 1 through 3, the value for the variables are given for you. So, for example I will work out problem #1 for you.
Y = 5x - This means that the value for Y is 5x. Now, your equation is 3x + Y = -96. As I said above, you must plug in the value of the variable. Meaning, where the variable Y sits in the equation, you must substitute it with 5x. So, your new equation would be 3x + 5x = -96. Next, you must add like-terms, which simply means you must add 3x & 5x together, which equals 8x. Now that you've added the like terms, your new equation is 8x = -96. Now, all you've got to do is divide both sides by 8, so as to get the variable X alone. Therefore the answer to #1 is X = -12. For the remaining two questions, you are to follow the same steps.
For questions 4 & 5, an alternate approach is necessary. For example, I will work out #4 for you.
First, you must subtract 6 from both sides, as this is the first step that is necessary to get the variable C alone. In doing so, the equation will now be -2c > 26. Taking it in mind that you are trying to get the variable C alone in the equation, you must now divide by sides by -2. Thus, your answer is C > -13. For question 5, use the same approach.
6 & 7 are slightly similar to questions 1 - 3, only you are trying to solve from the variable X in #6 & variable N in #7. I will solve #6.
To begin, you must subtract the 7 from both the left side & right side of the equation, setting up the left side to hold only the variable X, making the equation 3x = 5x - 10. Now, so as to get the variable X on one side, you must subtract 5x from both sides. Making the equation -2x = -10. As stated above, you must now divide both sides by -2 so as to get the variable X by itself. Therefore, the answer the #6 is X = 5.
2006-09-10 07:18:24
·
answer #1
·
answered by Houston B 1
·
0⤊
1⤋
In each of the problems, you need to substitute variables so that you are can solve the equation using only one of the variables.
For example, on problem #1, since y=5x, try substituting the y in the second equation so that you get 3x + (5x) = -96. Then combine the terms and solve for x. It's pretty much the same process for the rest of the equations.
The only difference on #4 and #5 is that c and x can have more than one answer. Try pretending that the > is an equal sign for a second and solve the problem. The answer then is any number less than the one you found.
Hope this helps, good luck!
2006-09-10 13:59:17
·
answer #2
·
answered by cushdogjr 3
·
0⤊
0⤋
1. 3x+5x= -96
8x= -96
x= -16
2. can you write it more detailed is mixed
3. 5-4= 50
1=50 no solution
4. 6-2c greater than 32
-6 -6
-2c = 26
c is less than -13
5. -6x less than -36
x is greater than 6
6. 3x+7 = 5x-3
-3x -3x
7= 2x-3
+3 +3
10=2x
x=5
7. 7=5n - 12n
7=-7n
n= -1
2006-09-10 14:06:15
·
answer #3
·
answered by juliotelehit 2
·
0⤊
0⤋
1. (*) y = 5x, (**) 3x + y = -96
sub (*) into (**)
(**) 3x + y = -96
(**) 3x + 5x = -96
(**) 8x = -96
--> x = -12
sub x = -12 into (*)
(*) y = 5x
(*) y = 5(-12)
--> y = -60
For 2 and 3 you can use the same approach.
4. 6 - 2c > 32
(6 - 2c) - 6 > 32 - 6
-2c > 26
(-2c)/-2 < 26/-2 (Note: the inequality sign flips when you divide or multiply by -1)
c < -13
Use the same approach for 5
6. 3x + 7 = 5x - 3
3x + 7 - 5x = 5x - 3 - 5x
-2x + 7 = -3
-2x + 7 - 7 = -3 - 7
-2x = -10
x = 5
Use the same approach for 7.
Good luck!
2006-09-10 13:58:25
·
answer #4
·
answered by Jess 2
·
0⤊
0⤋
1) y=5x...equation (i)
3x+y= -96....equation(ii)
therefore......by substituting equation(i) in (ii) we get:->
3x+5x= -96
8x= -96
x= -12 and y=5*-12
2) n=3p-4...equation(i)
2p-3n= -2..''(ii)
substituting (i) in (ii) we get:->
2p-(3p-4)=-2
2p-3p+4=-2
-p+4=-2
-p=-6
p=6 and n=22
3) 20-4m-50=0
4m+30=0
m=30/4
m=7(1/2)
4) 6-2c-32 > 0
2c+32 < 0
2c < -32 (signs changed)
c < -16
5) 6x > 36 (inequality sign changed)
x>6
6) 3x+7-5x+3=0
10-2x=0
x=10/2
x=5
7) 7=5n-12n
7= -7n
-n=1
n= -1(signs changed)
2006-09-10 14:07:02
·
answer #5
·
answered by tonima 4
·
0⤊
0⤋
Let's tackle 4 and 5. These seem to be the hardest
for you.
6 -2c > 32.
Let's subtract 6 from both sides
-2c > 26
Now let's divide both sides by -2.
When you divide both sides of an inequality by a negativee
number you must reverse the sense of the inequality.
So, c < -13.
Number 5 follows the same rule. Divide both
sides by -6 and x > 6.
Hope that helps a bit.
2006-09-10 14:15:37
·
answer #6
·
answered by steiner1745 7
·
0⤊
0⤋
1. substitute the 5x from equation one into the second.3x+5x = -96....8x = -96 then devide by 8. same for #2.
#3 just seems wrong.
#4 subtract 6 from both sides....-2c> 26 then devide by -2.......careful when deviding by a neg.... it changes the inequality sign...... c < -13 same with #5.
#6 get your like terms together..... 7 = 5x-3x -3....7=2x-3......7-3= 2x ....5 = 2x ...x=5/2 same for # 7.
2006-09-10 15:44:29
·
answer #7
·
answered by who be boo? 5
·
0⤊
0⤋
1) Y=5x 3x+y= -96 ...... ok, so the y=5x is the key, you plug it into the equasion..... 3x+(5x)= -96...... 8x= -96.. then divide both sides by 8... x= -12
2- sameway.. plug it in...
3same
hope that helps... its been a while, but im pretty sure thats all correct.
2006-09-10 13:56:34
·
answer #8
·
answered by Jill 2
·
0⤊
0⤋
1.y=5x
3x+5x=-96
x=-12
2.2p-3n=-2
6p-9n=-6
6p-2n=8
7n=-14 n=-2 so p=-4
3.m=4
5-m=50 the sum is wrong
4.6-2c>32
-2c>26
-c>13
c<13
5.6x>36
x>6
6.3x+7=5x-3
-2x=-10
x=5
7.-7n=7
n=-1
2006-09-10 13:58:38
·
answer #9
·
answered by raj 7
·
0⤊
0⤋
=ask your math teacher
2006-09-10 13:48:38
·
answer #10
·
answered by Anonymous
·
0⤊
1⤋